Regular physical exercise, sedentarism and characteristics of dismenorrhea and premenstrual syndrome - Lívio Matheus Aragão dos Prazeres; Renan Guedes de Brito; Erika Silva Ramos (Editora Champagnat, 2018)
Abstract Introduction: Among the menstrual disorders of the female reproductive period, Premenstrual Syndrome (PMS) and Dysmenorrhea are the most prevalent. The intensity of the signs and symptoms in each of these conditions may compromise the physical, psychological and social well-being of the woman at the stage of the menstrual cycle. Objective: To compare the signs and symptoms of menstrual disorders in women who practice regular exercise or not. Methods: A cross-sectional study carried out on women who practice exercises regularly and sedentary women. The IPAQ questionnaires and the evaluation of signs and symptoms of dysmenorrhea and PMS were applied to non-sedentary and sedentary students from the Federal University of Sergipe, Campus Lagarto. Results: Both groups had similar data for mean age and the mean Body Mass Index (BMI), therefore, passive of comparison. The prevalence of dysmenorrhea was significantly higher among sedentary women, 82% in the sedentary group and 46% in the non-sedentary group (p < 0.001), as well as some negative impacts on the psychological, social and physical state of both PMS and dysmenorrhea. Conclusion: The prevalence of signs and symptoms of dysmenorrhea was significantly higher in the Sedentary Group. Analyzing the behavior of PMS in relation to the practice of physical exercises, it was observed that the signs and symptoms of depressed mood, fatigue, difficulty to concentrate, lack of interest in social and home activities were more significant in the Sedentary Group.